(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
The objective of this article is to present a new class of vector interval-valued variational-like inequality problems. Based on the concepts of LU optimal and weakly LU optimal solutions, we derive some relations between the interval-valued programming and variational-like inequality problems. The study of the interplay between interval-valued optimization problems (IVOP) and vector variational-like inequalities (VVLI) combines theoretical advancements under the concept of differentiability and μ- invexity. Furthermore, to demonstrate the established linkages, we provide examples and an example demonstrates how well the vector variational inequality problems may be applied to deal with (MOIVP) problems.